A acústica do museu nacional Soares dos Reis, Porto - António P. O. Carvalho (2012)
The main objective of this study is to acoustically characterize the National Museum Soares dos Reis, in Oporto, Portugal. An acoustic analysis of the museum was held using objective parameters measured within the largest showrooms (RASTI, RT, background noise (LA,eq) and NC/NR). A brief subjective analysis by surveys was made after people visited the museum, which evaluated the acoustic quality of the museum. It was developed and applied a multicriteria methodology from various acoustic parameters (RT, RASTI, LAeq background noise with HVAC, L'nT,w, D2m,nT,w) in which the weight of the criteria was based on surveys conducted in the museum. Some measures of acoustical correction in the museums rooms are suggested.